Group Therapy Treatment for Food Selectivity (FS17-05-19) - Logie, Sean (Curr Dev Nutr, 2019)
OBJECTIVES: The purpose of this quality improvement project was to implement a group exposure therapy intervention to more efficiently serve the patients that are referred to our hospital due to severe food selectivity. METHODS: The intervention used evidenced-based practices such as systematic desensitization, a token economy, counterconditioning, and parent training to help patients expand their food repertoire. The intervention is a 12-week multi-family group therapy for children that range in age from 4–14. Patients are placed into groups of no more than six members of similar age. In 11 of the sessions, therapists direct patients through an exposure hierarchy with novel foods and record the number of bites patients take of each food. In 4–5 sessions, a psychologist meets with parents separately to discuss how to use exposure therapy to treat food selectivity. We examined data from the groups that ran from March 2016 to June 2018. RESULTS: Using a Wilcoxon Signed-Ranks Test, we compared the number of bites of novel foods that patients took in the first and last food exposure sessions. Results indicated that patients took significantly more bites of novel foods in the last group (median = 34) compared to the first group (median = 8.5), z = 4.79, P < .001. CONCLUSIONS: The outcomes of this project suggest that time-limited group interventions may help children who struggle with severe food selectivity. Time-limited groups also may also decrease treatment wait time for patients with severe food selectivity because patients can be seen simultaneously and with clear start and end date for the service. FUNDING SOURCES: N/A. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: